THROMBOSIS DAN USIA LANJUT - Bakta, I Made (journal of internal medicine, 2007)
Thrombosis, venous as well as arterial thrombosis, is the basic pathogenetic mechanism which leads to high morbidityand mortality diseases. The Virchow triad is the basic mehanism of pathogenesis of thrombosis, ie abnormality of vessel wall,disturbances of blood flow, and abnormality of blood coagulation (hypercoagubility state). The risk factors for thrombosis couldbe classified into 3 main categories: situational risk factors, hereditary thrombophilia, and acquired thrombophilia.The incidence of thrombosis is higher in old people, old age is categorised as one of the risk factors of thrombosis. Themechanism of old age in promoting thrombosis is not well understood. It is assumed that in old age there is imbalance betweenprotrombotic and antithrombotic factors, the increase of protrombotic factors are higher than antithrombotic factors.The increaseof coagulation factors (fibrinogen, prothrombin, factor VII, factor VIII, von Willebrand factor, and plasminogen activator inhibitor)were increased in old age population. Recently, the genetic mechanism of age regulation synthesis of factor IX and protein C wasfound.Atherothrombosis is a new concept, in which thrombus deposition occured on an atheromataous plaque. Atherothrombosisgives principal clinical manifestations as coronary artery disease, acute myaocardial infarction and unstable angina, ischaemicstroke, and peripheral arterial disease. Venous thrombosis, especially on deep vein, gives clinical manifestation as deep veinthrombosis (DVT), which is frequently followed by pulmonary emboli (PE). The combination of DVT and PE is known as venousthromboembolism (VTE).The concept of thrombosis management should be based on its pathogenesis. In arterial thrombosis, the main therapy isadministration of antiplatelet drug and anticoagulant to prevent the deposition of thrombus, while thrombolytic or fibrinolyticdrugs are given to dissolve the preformed thrombi. In venous thrombosis antiplatelet drug is not effective.Basically, the treatment of thrombosis in old age is not different from the treatment of thrombosis in general. But in oldpeople the comorbids are more frequent, drug interaction should be taken into special consideration.